Material Remains: Doris Salcedo. Issue 1 (July 2017) - Comay, Rebecca
Abstract : Doris Salcedo's artworks seem to confront the challenge that Adorno expressed so brutally: how to commemorate a traumatic event which both demands and refuses commemoration; where all available cultural forms threaten to trivialize, sentimentalize, mystify, embellish, instrumentalize, or otherwise betray the memory of the dead; and where every attempt to acknowledge injury seems only to compound it. On the one hand, it is the task of art to commemorate suffering. On the other hand, art, by its very existence—its status as a thing among things—is complicitous in this suffering. This essay reflects on the antinomies of mourning and politics in Salcedo's work.